2019
DOI: 10.1115/1.4045643
|View full text |Cite
|
Sign up to set email alerts
|

Study of Magnetic Field Effects on the Oxygen Transfer in Liquid Lead Cavity Flow Using the Lattice Boltzmann Method

Abstract: Natural convection and oxygen transfer characteristics in square cavity subjected to the magnetic field are studied numerically. Oxygen transfer in liquid metals has attracted much attention because it can decrease the corrosion rate of steel in contact with liquid metals. In advanced reactors, liquid lead has been utilized as an effective coolant. As indicated by many research reports that corrosion could be decreased by controlling the proper level of oxygen in the liquid lead. In this method, oxygen needs t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Many studies have reported that the behaviors of oxygen in water can be affected by an external magnetic field which would enhance the dissolving efficiency of the oxygen or the interface flow velocity 17 – 23 . Most of the results show that when a field strength less than 1 T is applied to the solution, the concentration of the dissolved oxygen is increased up to 50%.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have reported that the behaviors of oxygen in water can be affected by an external magnetic field which would enhance the dissolving efficiency of the oxygen or the interface flow velocity 17 – 23 . Most of the results show that when a field strength less than 1 T is applied to the solution, the concentration of the dissolved oxygen is increased up to 50%.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, many studies have reported that the behaviors of oxygen in water can be affected by an external magnetic field which would enhance the dissolving efficiency of the oxygen or the interface flow velocity [15][16][17][18][19][20][21] . Most of the results show that when a field strength less than 1T is applied to the solution, the concentration of the dissolved oxygen is increased up to 50%.…”
Section: Introductionmentioning
confidence: 99%